Encouraging Domestic Tourist;s Intention to Revisit Bali Thru The Mediation of Customer Satisfaction and Engagement - Febri Purnama Sari, Desak Made; Ni Luh Ria Sukmadani, Ria; Juwita Sari, Putu Ratna; Adyatna Wedananta, Kadek (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This research examines the impact of customer experience on the intentions of domestic tourist’s o revisit Bali, utilizing customer satisfaction and customer engagement as mediating. In this quantitative study, 400 Indonesian visitors with prior Bali travel experience participated using the Expectation Disconfirmation Theory methodology. The Partial Least Squares-Structural Equation Modeling (PLS-SEM) approach was used to analyze the data. According to the study's findings, customer experience has a major impact on engagement and satisfaction, both of which have a favorable effect on the intention to return. Engagement and satisfaction have been shown to be significant mediators in enhancing travelers' behavioral intentions. This study demonstrates how crucial emotional ties and the caliber of in-depth experiences are to fostering visitor loyalty to Bali. Practically speaking, in order to support the sustainability of domestic travel in Bali, tourism managers and legislators are encouraged to enhance service quality and produce unforgettable experiences.